Ayurvedic Management of Adenomyosis (AYUSHDHARA, 2024)
Adenomyosis is a gynecological condition with ectopic endometrial tissue in the uterine myometrium. This condition often results in symptoms such as heavy menstrual bleeding, dysmenorrhea, chronic pelvic pain, and can significantly impact a woman’s quality of life. If untreated, it can progress to endometriosis and require a hysterectomy. Adenomyosis has a prevalence of 9% in healthy individuals, but this increases to 70% in those with endometriosis. However, Ayurvedic formulations with properties like Anulomaka, Vatashamaka, Lekhana, and Balya can provide significant relief from pain and irregular menses, thus improves patient's quality of life. Background: A married Hindu female patient of 26 years came to NIA Prasuti-stri roga OPD on 22-02-24 with chief complaint of painful menses since menarche and associated complaint of small sized clots p/v (1st to 11th day) and brownish discharge p/v after 7 days of menses (8th to 11th day). Her sonography findings were suggestive of adenomyosis. Methodology: Mainly Vata dosha vitiation symptoms were observed in the patient. Her complete Nidana Parivarjana was done, also advised to follow Rajaswalacharya. Vatashamaka, Vatanulomak and Balya dravyas were used in treatment. The treatment was continued for 2 months. Result: There was significant relief in pain during menses, brownish discharge after 2 months of treatment. Her sonography findings were normal.